Tumor-Infiltrating Cytotoxic T Cells and Tumor-Associated Macrophages Correlate With the Outcomes of Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancer - Yang, Yuqin; Tian, Wenjing; Su, Liqian; Li, Peiqiu; Gong, Xiaohua; Shi, Lu; Zhang, Qingling; Zhao, Bin; Zhao, Hong (Frontiers in Oncology, 2021)
Background: Tumour-infiltrating immune cells (TIICs) play a key role in immunoregulatory networks and are related to tumour development. Emerging evidence shows that these cells are associated with sensitivity to chemotherapy and radiotherapy. However, the predictive role of TIICs in the outcomes of neoadjuvant chemoradiotherapy (nCRT) for locally advanced rectal cancer (LARC) is unclear. Methods: Imaging mass cytometry (IMC) was performed to comprehensively assess the immune status before nCRT in 6 patients with LARC (3 achieved pathological complete response (pCR), 3 did not) with matched clinicopathological parameters. Immunohistochemistry (IHC) for CD8, CD163 and Foxp3 on biopsy samples from 70 patients prior to nCRT and logistic regression analysis were combined to further evaluate its predictive value for treatment responses in an independent validation group. Results: A trend of increased CD8+ cytotoxic T lymphocytes (CTLs) and decreased CD163+ tumour-associated macrophages (TAMs) and Foxp3+ regulatory T cells (Tregs) in the pCR group was revealed by IMC. In the validation group, CTLs and TAMs were strong predictors of the clinical response to nCRT. High levels of CTLs were positively associated with the pCR ratio (HR=1.042; 95% CI: 1.015~1.070, p=0.002), whereas TAMs were correlated with a poor response (HR=0.969; 95% CI: 0.941~0.998, p=0.036). A high density of TAMs was also associated with an advanced cN stage. Conclusion: CTLs in the tumour microenvironment (TME) may improve the response to nCRT, whereas TAMs have the opposite effect. These results suggest that these cells might be potential markers for the clinical outcomes of nCRT and aid in the clinical decision-making of LARC for improved clinical outcomes.